Functional characterization of O-methyltransferases involved in biosynthesis of flavonoids in dwarf banana Musella lasiocarpa - Long Huang; Pirui Li; Junzhi Wu; Boya Feng; Mei Tian; Shu Xu; Wei Lyu; Xu Feng; Wanli Zhao; Yu Chen (Medicinal Plant Biology)
O-methyltransferases (OMTs) play a crucial role in the methylation of a range of secondary metabolites, such as phenylpropanoids, flavonoids, and lignins. However, the genetic mechanism underlying flavonoid methylation in the medicinal plant Musella lasiocarpa, a rich source of methylated flavonoids, remains to be elucidated. Here, we identified and characterized a new caffeic acid O-methyltransferase (COMT) enzyme, designated Ml05G3914, along with three other OMTs (Ml01G0494, Ml04G2958, and Ml08G0855), through genome and transcriptome association analysis. The potential role of MlOMT was studied by testing the catalytic activity of recombinant protein with numerous possible substrates in vitro. Our findings demonstrate that Ml01G0494, Ml04G2958, and Ml05G3914 are capable of catalyzing the monomethylation of baicalein, quercetin, luteolin, and caffeic acid as well as dimethylation of myricetin. Additionally, M1080855 can catalyze monomethylation of luteolin and caffeic acid and progressively facilitate the production of both mono-and di-methylated products of myricetin. This study provides insights into methylated flavonoid biosynthesis in M. lasiocarpa and might potentially contribute to the large-scale production of methylated flavonoids via biosynthesis approaches in the future.